Financing social security: simulating different welfare state systems for Germany - Caroline Dieckhöner; Andreas Peichl (Institute for the Study of Labor (IZA), 2009)
In Germany, there is an ongoing debate about how to increase the efficiency of the social security system and especially its financing. The aim of this paper is to simulate different financing systems for Germany. The introduction of a Liberal British or the Southern Greek financing system increases inequality and poverty, as well as labour supply incentives. The introduction of the Social-democratic Danish financing system decreases inequality of incomes, but does not necessarily lead to less poverty. Tax payments are extremely high, whereas social contribution payments are relatively low leading to mixed incentives effects.
urn:nbn:de:101:1-20090513333
Keywords: C81; D31; H24; 330; Social security; welfare states; comparative analysis; EUROMOD; Sozialversicherungsfinanzierung; Soziale Sicherung; Sozialstaat; Einkommensverteilung; Arbeitsangebot; Ökonomischer Anreiz; Simulation; Deutschland